A visualization of family relations inspired by the London Metro Map - Jan Korst; Verus Pronk; Jarke J. van Wijk (VINCI'20: Proceedings of the International Symposium on Visual Information Communication and Interaction, 2020)
We propose a new visualization of family relations, called family metro map, which is inspired by the famous London Underground Map. A family is represented by a metro line, where the parents are the end nodes and the children the intermediate nodes. We introduce family trees as rooted binary trees and consider the problem of automatically drawing a family metro map for a given family tree without crossing line segments, where the successive nodes of a metro line are placed at equal distances. The inter-node distance may be chosen to depend on the generation of the family, such that metro lines of earlier generations are shown more prominently than metro lines of later generations.